Highly efficient removal of organic dyes from waste water using hierarchical NiO spheres with high surface area - Zhu, Ting (2013)
A facile solvothermal method has been developed for large-scale preparation of uniform spheres of a nickel–ethylene glycol complex (Ni-EG complex) with a hierarchical nanostructure. The dispersibility and hierarchical structure of the Ni-EG particles can be tuned by varying the concentration of additives added. On the basis of experimental observations, a plausible mechanism has been proposed to understand the formation process of the Ni-EG complex spheres. Calcining these as-prepared Ni-EG complex spheres at 300 °C in air results in uniform porous NiO spheres with a high specific surface area of 222 m2 g–1. When served as the adsorbent for Congo red in water, the colloidal suspension of the as-prepared NiO hierarchical spheres exhibits a high adsorption capacity for the dye removal, suggesting their potential use in water treatment.